Superendividamento do Consumidor: os contratos de crédito pessoal por idosos e a responsabilidade penal do fornecedor - Queiroz, Sheyla Cristina Ferreira dos Santos (2016)
The overindebtedness reaches the consumer as an individual and as a social being. The constitutional principle of human dignity is infringed at the time when the consumer is hit by chronic indebtedness, not being able to pay current and future debts without affecting their livelihood or his family. Personal credit agreement may be a taxable event of over-indebtedness, it is the consumer burden your monthly budget with loans not leaving an amount sufficient to meet basic needs. The credit contract, consumers will receive the cash value of the car title loan and take payment through installments, with possible payroll deduction or current account. The elder, as a consumer, need greater legal protection before his hipervulnerabilidade, and thus, the Elderly Statute and the Consumer Protection Code (Law No. 8.078 / 90) are instruments that will promote this defense. It is noteworthy that the Elder is one of the biggest victims of indebtedness with a view to facilitating credit and the conduct that is practiced by the supplier when the contract does not adequately informing the elderly consumer, bypassing the legal limit for credit granting and enforcing compounded interest. Despite the vendor's conduct of gravity and the effects of the elderly consumer the State has not criminalized such practices as criminal omitting as to criminal responsibility. However, the legal framework of such conduct on some existing criminal types from crimes against consumer relations as a way to temporarily resolve the conflict is possible.